Bleeding Events Following Concurrent Use of Warfarin and Oseltamivir by Medicare Beneficiaries. (November 2013) - Mosholder, Andrew D.; Racoosin, Judith A.; Young, Stephanie; Wernecke, Michael; Shoaibi, Azadeh; MaCurdy, Thomas E.; Worrall, Christopher; Kelman, Jeffrey A.
Background: During the 2009 H1N1 influenza pandemic, the UK Medicines and Healthcare Products Regulatory Agency received case reports suggesting a potentiation of warfarin anticoagulation by the antiviral drug oseltamivir. We evaluated this putative interaction using Medicare data.Objective: To determine the frequency of bleeding following addition of oseltamivir or comparator drugs among Medicare beneficiaries taking warfarin.Methods: This was a retrospective cohort evaluation using Medicare nationwide data. Cohort members were Medicare Parts A, B, and D beneficiaries from June 30, 2006 to October 31, 2010 receiving warfarin for at least 1 month prior to a concomitant drug of interest (oseltamivir, ampicillin, trimethoprim–sulfamethoxazole (TMP-SMX), and angiotensin-converting enzyme (ACE) inhibitors). Bleeding within 14 days of new prescriptions for oseltamivir or comparators was identified using inpatient or emergency department ICD-9 (International Classification of Diseases, ninth revision) discharge diagnosis codes for gastrointestinal hemorrhage, epistaxis, hematuria, and intracranial bleeding. Patients with bleeding within 30 days preceding the prescription concomitant to warfarin were excluded.Results: With concomitant ACE inhibitors as reference, adjusted odds ratios (ORs) for any bleeding events within 14 days were 1.47 (95% confidence interval [CI] = 1.08-1.88), 1.24 (95% CI = 0.97-1.57), and 2.74 (95% CI = 2.53-3.03), for warfarin plus ampicillin, oseltamivir, and TMP-SMX, respectively. In a sensitivity analysis, adjusted ORs over a 7-day period were 1.89 (95% CI = 1.29-2.59), 1.47 (95% CI = 1.06-2.02), and 3.07 (95% CI = 2.76-3.49) for warfarin plus ampicillin, oseltamivir, and TMP-SMX, respectively.Conclusions: Bleeding with oseltamivir plus warfarin was not significantly increased over a 14-day observation period; a sensitivity analysis showed a statistically significant increase over a 7-day period; in contrast, the data consistently showed the known tendency of TMP-SMX to potentiate the effects of warfarin. The results should be interpreted with the limitations of this approach in mind, including the inability to control for unmeasured confounders.